Answer:
0.485 lb
6.83 lb - 3.57 lb = 3.26 lb
3.26 lb - 0.35 lb = 2.91 lb
2.91 lb / 6 = 0.485 lb
1) yes
2) no
3) a. yes
b. no
3) you have two question #3's...
4) Do your own homework
Answer:
Enlargement by a scale factor of 3 centre (1,0)
Step-by-step explanation:
Answer:yes
Step-by-step explanation:Bc I am right and right
Answer:
![6^{4}](https://tex.z-dn.net/?f=6%5E%7B4%7D)
Step-by-step explanation:
using the rule of exponents
= ![a^{(m-n)}](https://tex.z-dn.net/?f=a%5E%7B%28m-n%29%7D)
note that 6 =
, then
=
= ![6^{4}](https://tex.z-dn.net/?f=6%5E%7B4%7D)